SELF-MICRO EMULSIFYING DRUG DELIVERY SYSTEM OF URSOLIC ACID: FORMULATION DEVELOPMENT, CHARACTERIZATION, PHARMACOKINETIC AND PHARMACODYNAMIC STUDIES FOR DIABETIC COMPLICATIONS - MOULI, GOLLA CHANDRA; VEERESHAM, CIDDI (International Journal of Applied Pharmaceutics, 2022)
Objective: The objective of this study was to develop, characterize, and conduct pharmacokinetic and pharmacodynamic studies on ursolic acid solid self microemulsifying drug delivery system (UA-S-SMEDDS) for the treatment of diabetic complications. Methods: Liquid self microemulsifying drug delivery system (L-SMEDDS) were made with Capryol 90 as an oil, Cremophor EL as a surfactant, and polyethylene glycol (PEG) 400 as a co-surfactant. The surfactant and co-surfactant (Smix) ratios were calculated using a pseudo ternary phase diagram. At different pH levels and with water, the globule size, polydispersity index (PDI), zeta potential (ZP), and dilution were all assessed. S-SMEDDS has developed adsorption to a solid carrier by utilizing L-SMEEDS formulation. The powder properties, liquid retention potential, globule size, PDI, ZP, assay, and pharmacokinetic studies were all evaluated. The pharmacodynamic investigations of the S-SMEDDS formulation in streptozotocin (STZ) induced Wistar rats were evaluated using malondialdehyde (MDA) and glutathione (GSH) determination in tissues and section studies. Results: S-SMEDDS formulation was successfully developed with a droplet size of 163.4±1.475 nm, PDI of 0.251±0.042, a ZP of-21.3±1.02, an assay of 96.21±0.75%. The release studies showed 26.28% (0.1N HCl) and 83.57% (6.8 phosphate buffer) were released in 15 min. When comparing the pharmacokinetics of a UA-loaded S-SMEDDS to the coarse suspension, the S-SMEDDS (F2A) showed a 4.12 fold improvement in UA oral bioavailability. The pharmacodynamic results showed that S-SMEDDS was a higher recovery rate. Conclusion: The developed solid SMEDDS (F2A) formulation proved effective in treating diabetic complications in STZ induced Wistar rats by inhibiting the aldose reductase enzyme.